Inhibitory effect of leaf extract of Newbouldia laevis on the metabolic activities of alpha-glucosidase and alpha-amylase - Kolawole, Oyetunji T.; Akanji, Musbau A. (Bangladesh Journal of Pharmacology, 2013)
In this study, the effect of ethanol extract of the leaves of Newbouldia laevis on the activity of α-amylase and α-glucosidase was investigated. Inhibitory effect of N. laevis extract on α-glucosidase was tested in vitro using baker's yeast α-glucosidase and rat intestinal α-glucosidase while α-amylase inhibitory effect was assayed using rat pancreatic α-amylase. α-Glucosidase inhibitory effect of the extract was also tested in vivo in diabetic and non-diabetic rats. N. laevis extract exhibited good α-glucosidase inhibitory activity in vitro with IC50 values of 2.2 µg/mL and 43.5 µg/mL for baker's yeast and rat intestinal α-glucosidase respectively. The extract also inhibited rat pancreatic α-amylase activity with IC50 value of 58.7 µg/mL. In both diabetic and non-diabetic rats, N. laevis extract caused a significant reduction in postprandial blood glucose level after oral sucrose load. The results of this study indicate that N. laevis extract exerts its glucose-lowering effect through inhibition of α-glucosidase and α-amylase.